2014
DOI: 10.1186/2052-0492-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of yamakagashi (Rhabdophis tigrinus) bites: a national survey in Japan, 2000–2013

Abstract: BackgroundYamakagashi (Rhabdophis tigrinus) is a species of pit viper present throughout Russia and Eastern Asia. Although R. tigrinus venom is known to induce life-threatening hemorrhagic symptoms, the clinical characteristics and effective treatment of R. tigrinus bites remain unknown. The present study aimed to clarify these issues.MethodsRecords in the Japan Snake Institute between 2000 and 2013 were retrospectively investigated. The following were determined: patient characteristics, coagulation and fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Several cases of Rhabdophis tigrinus bites have been reported in Japan but very few cases of Rhabdophis subminiatus bites have been reported (3) (4) . The bites of colubrid snakes can lead to severe envenoming, but the symptoms of such bites might be delayed for hours or days after the actual bite (2) .…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of Rhabdophis tigrinus bites have been reported in Japan but very few cases of Rhabdophis subminiatus bites have been reported (3) (4) . The bites of colubrid snakes can lead to severe envenoming, but the symptoms of such bites might be delayed for hours or days after the actual bite (2) .…”
Section: Discussionmentioning
confidence: 99%
“…1 Although R. tigrinus bites induces lifethreatening injuries, their mechanism and treatment have not been examined because of the extremely rare incidence of severe cases (nine cases reported over the past 13 years), compared with that of bites from G. blomhoffii and P. flavoviridis. 1,3,4 Our former survey indicated that the pathophysiology of R. tigrinus bites was considered disseminated intravascular coagulation (DIC) with a fibrinolytic phenotype; however, the details of coagulation markers remain unknown. Moreover, although antivenom therapy prepared from hyperimmunized horses (antivenin serum therapy) is established against R. tigrinus bites, sufficient information regarding antivenom therapy has not been provided in clinical practice.…”
Section: Y Amakagashi (Rhabdophis Tigrinusmentioning
confidence: 99%
“…Moreover, although antivenom therapy prepared from hyperimmunized horses (antivenin serum therapy) is established against R. tigrinus bites, sufficient information regarding antivenom therapy has not been provided in clinical practice. 3,5 Here we describe the trends of coagulations markers in the case of R. tigrinus bites and highlight the antivenom therapy for R. tigrinus.…”
Section: Y Amakagashi (Rhabdophis Tigrinusmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rhabdophis tigrinus (Yamakagashi snake) bites or gas gangrene require an immediate administration of the antivenom to save the patient's life. However, inadequate supply planning has resulted in insufficient storage sites, which in turn leads to delays in the delivery of medication to patients …”
Section: Introductionmentioning
confidence: 99%